Identifying Constraints on Everyday Clinical Practice: Applying Work Domain Analysis to Emergency Department Care. (February 2022) - Austin, Elizabeth; Blakely, Brette; Salmon, Paul; Braithwaite, Jeffrey; Clay-Williams, Robyn
Background: Emergency departments (EDs) are complex socio-technical work systems that require staff to manage patients in an environment of fluctuating resources and demands. To better understand the purpose, and pressures and constraints for designing new ED facilities, we developed an abstraction hierarchy model as part of a work domain analysis (WDA) from the cognitive work analysis (CWA) framework. The abstraction hierarchy provides a model of the structure of the ED, encompassing the core objects, processes, and functions relating to key values and the ED's overall purpose. Methods: Reviews of relevant national and state policy, guidelines, and protocol documents applicable to care delivery in the ED were used to construct a WDA. The model was validated through focus groups with ED clinicians and subsequently validated using a series of WDA prompts. Results: The model shows that the ED system exhibits extremely interconnected and complex features. Heavily connected functions introduce vulnerability into the system with function performance determined by resource availability and prioritization, leading to a trade-off between time and safety priorities. Conclusions: While system processes (e.g., triage, fast-track) support care delivery in ED, this delivery manifests in complex ways due to the personal and disease characteristics of patients and the dynamic state of the ED system. The model identifies system constraints that create tension in care delivery processes (e.g., electronic data entry, computer availability) potentially compromising patient safety. Application: The model identified aspects of the ED system that could be leveraged to improve ED performance through innovative ED system design.